Potential of Siam Weed Leaves (Chromolaena odorata) in Suppressing Anthracnose Disease (Colletotrichum gloeosporioides) in Shallot (Allium ascalonicum L.) in In Vitro - Mayasari, Paulina Akita; Abadi, Abdul Latief; Choliq, Fery Abdul (Journal of Tropical Plant Protection, 2023)
Anthracnose disease (Colletotrichum gloeosporioides) is one of the important diseases in shallots. Generally, farmers use synthetic fungicides. Thus, Siam weed (Chromolaena odorata) leaf extract can be used to reduce it because it has antifungal compounds. This study aimed to examine the effect of siam weed leaf extract on the growth of C. gloeosporioides and its antifungal compounds. This research used a completely randomized design (CRD). It would be continued with the SRD test at the 5% level if the result was significantly different. Treatment consisted of 0, 2, 4, 6, 8, and 10% Siam weed leaf extract with four replications. Bioactive compounds in siam weed leaves were tested by the UPT Herbal Materia Medica Batu Laboratory and Chem-Mix Pratama Laboratory, Yogyakarta. Probit analysis was also used to obtain the LC50 value. The results showed that 10% concentration was the most effective treatment because it produced a fungicidal effect on C. gloeosporioides. However, a 2.09% concentration of siam weed leaf extract was able to cause 50% of C. gloeosporioides' mortality. In addition, siam weed leaf extract contains antifungal compounds, such as tannins, phenols, flavonoids, alkaloids, and saponins.